2018
DOI: 10.1007/s10549-018-4664-7
|View full text |Cite
|
Sign up to set email alerts
|

The PDGF pathway in breast cancer is linked to tumour aggressiveness, triple-negative subtype and early recurrence

Abstract: PurposeThe platelet-derived growth factor (PDGF) signalling pathway is often dysregulated in cancer and PDGF-receptor expression has been linked to unfavourable prognostic factors in breast cancer (e.g. ER negativity, high Ki67 and high grade). This study aimed to evaluate the expression of PDGFRα, PDGFRβ and ligand PDGF-CC in breast cancer in relation to molecular subtypes and prognosis.MethodsProtein expression of tumour and/or stromal cell PDGFRα, PDGFRβ and PDGF-CC was evaluated in primary tumours (N = 489… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 31 publications
(41 reference statements)
0
55
0
1
Order By: Relevance
“…EGFR is a hall-mark of basal like breast cancer and has repeatedly been presented as a key player promoting EMT [49,50]. Interestingly, PDGFC is also associated with features of inferior prognosis in human breast cancer [27] and the PDGFC gene strongly correlates with gene-sets defining the EMT pathways supporting an association also for PDGFC with EMT [51]. The functional role of PDGFC in the EMT promoting process is, however, not settled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR is a hall-mark of basal like breast cancer and has repeatedly been presented as a key player promoting EMT [49,50]. Interestingly, PDGFC is also associated with features of inferior prognosis in human breast cancer [27] and the PDGFC gene strongly correlates with gene-sets defining the EMT pathways supporting an association also for PDGFC with EMT [51]. The functional role of PDGFC in the EMT promoting process is, however, not settled.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Lund University ethics committee (LU699-09, LU75-02), and all patients included provided written informed consent. Results of the observational study and information about the patient cohort have been described, including biomarker protocols and assessment, in detail previously [25][26][27]. Patients diagnosed with lobular carcinomas were excluded in the present study, as several studies have demonstrated a different expression pattern of E-cadherin in this type of breast cancer [28][29][30].…”
Section: Patientsmentioning
confidence: 99%
“…A recent study reporting immunohistochemical analyses of a cohort of 550 human breast cancer samples including 30 TNBCs reported expression of PDGFRβ in the stroma and not in tumor cells 56 , and suggested that the paracrine crosstalk existing between basal-like mammary cancer cells, expressing the PDGF-CC ligand, and cancer-associated fibroblasts, expressing both PDGFRβ and the cognate PDGFRα 57 , could be the most prominent route of PDGFR-dependent signal transduction in breast cancer. Herein, by extending the analysis on a TMA comprising 200 cases of human TNBC, we present novel data showing that PDGFRβ is also expressed in tumor cells belonging to a restricted subgroup of tumors of the mesenchymal subtype expressing either MMP-9 or ALDH proteins that appears as a highly invasive and stem-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the current study, PDGFRB was demonstrated as an additional FA gene associated with GPER. Although the role of the PDGFB/PDGFRB axis in BC progression is still a subject of debate, PDGFRB overexpression was correlated with the acquisition of vascular-like functional properties of TNBC, suggesting its involvement in tumor aggressiveness [77,78]. From our correlation and pathway analysis, two members of the ECM-receptor interaction and the FA pathway, named PGF and VWF, which were indicated as prognostic markers in BC [79,80], appeared to be associated with GPER.…”
Section: Discussionmentioning
confidence: 73%